Analisis Dampak Program Hutan Kemasyarakatan (HKM) KTH Alue Simantok Aceh Terhadap Kelestarian Hutan Dan Sosial Ekonomi Masyarakat - Dailami; Satriawan, Halus; Abbas, Rahmat; Azizah, Cut (Future Academia : The Journal of Multidisciplinary Research on Scientific and Advanced, 2024)
Social forestry is a sustainable forest management system. HKm Alue Simantok, located in Peudada District, Bireuen Regency, Aceh Province, is a social forestry scheme with IUPHKm (Community Forest Utilization Business Permit). This research aims to analyze and identify the impact of the community forest program (Hkm) for the Alue Simantok forest farmer group on forest and socio-economic sustainability as well as to analyze and identify strategies that need to be implemented in controlling the community forest program (Hkm) for the Alue Simantok Forest Farmer Group. Forest Sustainability and Socio-Economics. The research approach uses quantitative descriptive research methods that focus on field research by exploring data sourced from members of forest farmer groups and communities living around the Alue Simantok Forest area as well as practitioners working in the forestry sector. The research results show that the HKm program has an impact on improving the economy, preserving forests and is socially acceptable to the community. It is certain that the Alue Simantok Hkm can be sustainable and it is recommended that there be a social forestry model developed so that the economic value of the forest can continue to be maintained.